Publiczne zarządzanie kryzysowe w działalności instytucji finansowych - Janusz Zawiła-Niedźwiecki; Antoni Rakoczy (Studia i Materiały)
As a result of the evolution of public crisis management (from providing security to the direction of guaranteeing the comfort of social life), financial institutions are gradually being recognized as crucial for the provision of public services in emergency situations, ie. the so-called “operators of critical infrastructure of the state”, and therefore increasingly charged with new responsibilities, in the field of public crisis management. The article demonstrates how R&D projects bring to the sphere of public crisis management methodological approach similar to operational risk management in the sphere of purely business. The article presents: analogies between public crisis management and operational risk management; the essence of social logistics, which part consists the public crisis management; and methodical logic emergency response.